Share bidding auctions, sliding scale royalty rates and the new brazilian regulatory framework for the pre-salt areas - Damé, Otávio Menezes (2014)
Brazilian government recently passed legislation instituting a new regulatory framework for the pre-salt reserves. These areas should be negotiated through a profit-share bidding auction. Motivated by this new rules, we present a model of share bidding auction under affiliation, demonstrating the existence of a monotone pure-strategy equilibrium in this structure and characterize its equilibrium bidding function. In addition, we prove that it generates an expected revenue at least as large as the usual fee bidding auction. Next, we introduce in the models a function representing a royalty rate that is contingent to the value of the object. This instrument permits an improvement of expected revenue of both models, making the gap between them shrink. Finally, analyzing this new regulatory framework from the viewpoint of the theoretical and numerical results obtained, we conclude that the former oil regime was more appropriate and lucrative to Brazilian government.